Pengembangan Budaya Disiplin pada MTsN Tunggangri, MTsN Tulungagung, dan MTsN 2 Kota Kediri - Khoirul Anam (Ta'allum: Jurnal Pendidikan Islam, 2018)
Every successful education institution must have cultivated good cultures, one of them is a culture of discipline. According to the three steps theory of Kurt Lewin, there are some steps needed to develop the disciplinary culture: unfreezing, movement, and refreezing. The study belongs to a multi-sites design with qualitative approach. The data of the study are collected by employing the following three methods: in-depth interview, participant-observation, and documentation. The collected data are, then organized, interpreted, and analyzed in recursion. The activity of analyzing the data is done in every site and a cross-site analysis to formulate concepts and findings. The overall findings of the study are, the steps in developing a culture of discipline are carried out within five phases: (1) having a desire of changes supported by the value of being religious, the existence of external challenges and the availability of great desire of the leader; (2) preparing a good system done through building system and mindset of the disciplinary culture; (3) unfreezing the system conducted through the process of socialization which is continuously done and  followed by giving reward and punishment; (4) conducting movement realized by changing the disciplinary culture in terms of arrival, clothing, driving, and behaving in daily life; (5) refreezing the culture done to refreezing the existing culture of discipline covering the discipline of time, clothing, learning, driving, and behaving. The roles of the schools’ members in developing the culture of discipline are represented by school leaders as the ones responsible for making changes in relation to policy and coordination, the teachers and staff as agents of changes in implementing and controlling the culture of discipline, and the students as parts of object and evaluators of changes. Some efforts taken to overcome the resistance of the development of the culture of discipline coming from teachers and students are personally done both curatively and preventively. This study develop and support Kurt Lewin’s theories- the three step theory and the force field theory. These theories are also appropriate with the role theory developed by Biddle and Thomas. This study also indicates that religion takes an important role in cultivating and developing a culture of school discipline through modeling and habit approaches.